Learning together by means of Reading (2023)
This paper shows how reading short stories in English improved some abilities like oral interaction and reading comprehension in the first semester of Business Administration at a public university in Fusagasugá, Cundinamarca. It was qualitative work is framed in the Action Research. In this work, ten workshops focused on cooperative learning were developed to promote students’ skills in English class. However, although some difficulties were observed when students worked in teams, the development of the workshops favored personal aspects such as self-esteem, inter- and intrapersonal relationships and stimulated constructive attitudes towards cooperative learning.